ASSA14-13-01 Cigarette smoking-induced LDL dysfunction is partially reversible after smoking cessation. (1st December 2014) - Zhang, Y; Chen, LF; Feng, C; Wu, WL; Yan, XW
Abstract : Background: Increased level of low-density lipoprotein (LDL) is a well-established risk factor of atherogenesis. Cigarette smoking leads to endothelial dysfunction, an early event of atherogenesis. Objective: To investigate the effect of smoking and smoking cessation on the atherogenesis of LDL and possible differences of this effect between long-term smokers with and without CAD Methods: Human umbilical vascular endothelial cells (HUVECs) were treated with 50 and 100 μg/ml LDL isolated from long-term smokers with or without coronary artery disease (CAD), before and after smoking cessation. Functional changes of HUVECs were evaluated by measuring oxidative markers (MDA, LOX-1), NO, eNOS and inflammatory markers (TNF-α, IL-1β, MMP-9). Results: PlasmaLDL levels of long-term (>10 years) smokers were significantly higher than that of non-smokers (p < 0.05). Smoking modified LDL increased endothelial LOX-1 and MDA levels, the higher level of LDL leaded to significantly higher levels of LOX-1 and MDA (p < 0.05). And 90 days'cessation partially yet significantly reversed LOX-1 levels (p < 0.05) but not MDA levels. Smoking modified LDL increased endothelial IL-1β, TNF-αand MMP-9 levels (all p < 0.05), the higher level of LDL leaded to significantly higher levels of IL-1β, TNF-α and MMP-9 (all p < 0.05). And 90 days' cessation partially yet significantly reversed IL-1β, TNF-α and MMP-9 levels (all p < 0.05). LDL isolated from long-term smokers with CAD before cessation resulted in higher levels of IL-1β but lower levels of TNF-αand MMP-9 (all p < 0.05) compared to LDL isolated from long-term smokers without CAD before cessation. Smoking modified LDL decreased endothelial eNOS and NO levels (all p < 0.05), the higher level of LDL leaded to significantly lower levels of eNOS and NO (all p < 0.05). And 90 days cessation significantly increased eNOS (p < 0.05) levels and trends to decrease NO levels. Conclusion: Long-term cigarettes smoking had significant pro-oxidative and pro-inflammatory effects on LDLparticles which could lead to endothelial dysfunction. The detrimental effects of smoking on LDL could be partially reversed by 90days' smoking cessation.